2015
DOI: 10.4049/jimmunol.1402381
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Phenotypes of Human Regulatory T Cells Expressing the Receptors TIGIT and CD226

Abstract: Regulatory T cells (Treg) play a central role in counteracting inflammation and autoimmunity. A more complete understanding of cellular heterogeneity and the potential for lineage plasticity in human Treg subsets may identify markers of disease pathogenesis and facilitate the development of optimized cellular therapeutics. To better elucidate human Treg subsets, we conducted direct transcriptional profiling of CD4+FOXP3+Helios+ thymic-derived Treg (tTreg) and CD4+FOXP3+Helios− T cells, followed by comparison t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
189
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(200 citation statements)
references
References 50 publications
9
189
0
2
Order By: Relevance
“…However, the inverse correlation between IL-10 production and the Treg signature genes in our analysis is consistent with the recent report on human Treg cells in which IL-10 expression is inversely correlated with the Foxp3 and Helios expression (45). In addition, unlike the observation in mice, we were not able to demonstrate any correlation between a typical Th-specific transcription factor and the suppression of Th-specific cytokines (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…However, the inverse correlation between IL-10 production and the Treg signature genes in our analysis is consistent with the recent report on human Treg cells in which IL-10 expression is inversely correlated with the Foxp3 and Helios expression (45). In addition, unlike the observation in mice, we were not able to demonstrate any correlation between a typical Th-specific transcription factor and the suppression of Th-specific cytokines (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Thus, TIGIT signaling in Tregs may favor Treg stability. In line with this observation, TIGIT expression has recently been shown to correlate strongly with a stable Treg phenotype in humans (14). Importantly, several of the Figure 3A and Supplemental Table 1).…”
Section: 5supporting
confidence: 56%
“…Interestingly, while TIGIT + CD8 + TILs exhibited deficits in proinflammatory cytokine production, we found that they had significantly increased production of the immune-suppressive cytokine IL-10 compared with TIGIT -CD8 + TILs. Moreover, we found that TIGIT + CD8 + TILs exhibited a reduced capacity to degranution to direct regulation of effector T cell responses, recent studies show that TIGIT marks a subset of Tregs that exhibit heightened expression of known Treg effector molecules and heightened suppressive capacity in vitro (12,14). Most interestingly, TIGIT + Tregs exhibit a specialized function, that of selectively suppressing proinflammatory Th1 and Th17 responses but sparing Th2 responses (12), thus supporting a role for TIGIT in directing Treg function.…”
Section: Introductionmentioning
confidence: 83%
“…It is now clear that much complexity in the Treg phenotype exists than originally appreciated, and a growing number of other cell surface markers are found on specific Treg subsets, for example TIGIT,11, 12 GARP,13, 14, 15, 16 CD73 and CD39 17, 18. These markers are frequently also found on effector cell populations, and an emerging theme is that either Treg are able to transition between functional states or that the Treg compartment is paired with the Tconv effector compartment so that any immune response mediated by a T‐cell can be controlled by a matching Treg 19.…”
Section: Introduction: the Treg Phenotypementioning
confidence: 99%